1980
DOI: 10.1111/j.1365-2141.1980.tb06010.x
|View full text |Cite
|
Sign up to set email alerts
|

Non‐spherocytic Haemolytic Anaemia in Mother and Son Associated with Hexokinase Deficiency

Abstract: The case history, laboratory findings and properties of the enzyme in a patient with hexokinase deficiency are reported. The mother had a haemolytic disorder of similar severity. In these cases the expression of the disease in both mother and son suggests a dominant mode of inheritance. This family further illustrates the necessity of taking the reticulocyte level into account when interpreting red cell enzyme levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

1985
1985
2006
2006

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…This fact seems to indi cate that the main mechanism of anemia in hexoki nase deficiency is probably mediated by an increased phagocytosis of enzyme-deficient cells rather than hemolysis itself. Pieces of evidence that favor this conclusion are, certainly, the increased number of au tologous IgG that are bound to antihexokinase-IgGloaded erythrocytes (table 5), the observation by Newman et al [26] that in vitro a marked phagocyto sis of hexokinase-deficient cells was observed, and the observation that splenectomy usually stabilizes blood hemoglobin concentration and makes blood transfu sions unnecessary [21,22,[25][26][27][28]. Thus, hexokinase deficiency causes a cellular ATP depletion and favors autologous IgG binding and phagocytosis.…”
Section: Discussionmentioning
confidence: 87%
“…This fact seems to indi cate that the main mechanism of anemia in hexoki nase deficiency is probably mediated by an increased phagocytosis of enzyme-deficient cells rather than hemolysis itself. Pieces of evidence that favor this conclusion are, certainly, the increased number of au tologous IgG that are bound to antihexokinase-IgGloaded erythrocytes (table 5), the observation by Newman et al [26] that in vitro a marked phagocyto sis of hexokinase-deficient cells was observed, and the observation that splenectomy usually stabilizes blood hemoglobin concentration and makes blood transfu sions unnecessary [21,22,[25][26][27][28]. Thus, hexokinase deficiency causes a cellular ATP depletion and favors autologous IgG binding and phagocytosis.…”
Section: Discussionmentioning
confidence: 87%
“…The patient's cells appear to concentrate in the 2-3 lightest cell fractions, as is evident from the extreme pyruvate kinase deficiency measured in these cells. Compared to the activity of the enzyme hexokinase, which is noted for its high activity in premature red cells [11, 16,17] and compared to the activity in the corresponding fractions of patients with hemolytic anemia of nonmetabolic etiology and reticulocytosis, it was estimated that the residual pyruvate kinase activity in these cells is less than 2% of normal.…”
Section: Discussionmentioning
confidence: 99%
“…Fractions from 1 to h represent red cells of increasing density (age). produce phenotypic heterogeneity (Paglia et ul, 1981;Newman et al, 1980;Rijksen & Staal, 1978). However, recent results from this laboratory have proved that all multiple forms of human erythrocyte hexokinase possess similar kinetic and regulatory properties (Stocchi et al, 1982) and that all HK isozymic forms increase in trisomy of HK gene (Magnani et al, 1983).…”
Section: Discussionmentioning
confidence: 99%
“…In some cases the mutant enzyme was found to show modified substrate affinities (Keitt, 1969;Moseretal. 1970:Nechelesetal, 1970:Goebeletal, 1972:Siimesetul, 1979Newman et ul, 1980), in others reduced heat stability (Keitt, 1969;Board et al, 1978: Newman et al, 1980, or modified regulatory properties (Rijksen & Staal, 1978: Rijksen et al, 1983. Few papers report only a reduced enzyme activity with no additional enzyme abnormalities (Beutler et al, 1978;Paglia et ul, 1981).…”
mentioning
confidence: 99%